2009
DOI: 10.1142/s0218127409024463
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude Equation for Stationary Convection in a Rotating Binary Ferrofluid

Abstract: We report both theoretical and numerical results on convection for a binary magnetic mixture under rotation. We focus on the stationary convection for idealized boundary conditions. We obtain explicit expressions of convective thresholds in terms of the control parameters of the system. Close to bifurcation, the coefficients of the corresponding amplitude equation are determined analytically. The effect of the magnetophoresis and Kelvin force are emphasized and, finally, the nature of the bifurcation is discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The main objective of a weakly nonlinear analysis is to obtain an evolution equation for this unknown amplitude function. This method has been applied to a number of specific examples in physics, including shear flows, shallow water waves, thermoacoustics and magnetohydrodynamics; see, for example [32][33][34][35][36][37][38]. In these examples, the nature of the equations analysed means that the algebra often becomes very complicated.…”
Section: Weakly Nonlinear Stabilitymentioning
confidence: 99%
“…The main objective of a weakly nonlinear analysis is to obtain an evolution equation for this unknown amplitude function. This method has been applied to a number of specific examples in physics, including shear flows, shallow water waves, thermoacoustics and magnetohydrodynamics; see, for example [32][33][34][35][36][37][38]. In these examples, the nature of the equations analysed means that the algebra often becomes very complicated.…”
Section: Weakly Nonlinear Stabilitymentioning
confidence: 99%
“…For idealized boundary condition for the typical conductive state in the stationary case an analytical expression was found for the Rayleigh number as function of control parameters [30]. Recently, the weakly nonlinear analysis for stationary convection in a rotating magnetic binary mixture was studied [31]. Other effects, such as the buoyancy-surface tension effects, non-uniform thermal gradients, magnetization constitutive equations, etc., have also been studied in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…For their study, the explicit expressions of stationary convection thresholds have been demonstrated according to the parameters of the system. Interesting studies on convection in ferrofluids and for various situations have been theoretically conducted in [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%